Understanding student-centred learning in higher education: students’ and teachers’ perceptions, challenges, and cognitive gaps - Trinidad, Jose Eos R (Archīum Ateneo, 2019)
Student-centred learning (SCL) is often understood differently by people, and the differences are even more salient in higher education, where there are some very strong advocates and vocal critics. Theoretical research on SCL in higher education often highlights five key aspects but these have not been empirically scrutinised. Qualitative research with students and faculty from a large private university in the Philippines shows that there are particular facets of SCL that faculty and students eagerly subscribe to, particularly in terms of class engagement, skills building, and having motivated students. However, they fail to readily question how assessments and power relations between teachers and students are part of SCL. It suggests that SCL is viewed and reduced to effective classroom practices that have little to do with more foundational aspects of the teacher–student relationship and manifold possibilities for learning.